Experimental and numerical investigations into leakage behaviour of a novel prefabricated utility tunnel. (October 2020) - Lin, Zhenzhen; Guo, Chengchao; Ni, Pengpeng; Cao, Dingfeng; Huang, Liang; Guo, Zhufeng; Dong, Pu
Highlights: A novel prefabricated utility tunnel with either L-shaped or F-shaped wall is proposed. Influence of "wall chamfer" on longitudinal equivalent flexural stiffness is negligible. Leaking threshold of internal pressure for prefabricated utility tunnel is 0.45 MPa. Prefabrication can affect the structural integrity of utility tunnel to some extent. Leakage never occurs for utility tunnel with a normal burial depth of less than 13 m. Abstract: The form of utility tunnel is increasingly used nowadays for urban development. Considering the ease and the speed of construction, a novel prefabricated utility tunnel structure is proposed. Analytical calculation is conducted to derive the longitudinal equivalent flexural stiffness, from which the design detail of "wall chamfer" is found to have minimum influence. The leakage behaviour of the proposed prefabricated utility tunnel is evaluated by sealing test. The leaking threshold of internal pressure for prefabricated utility tunnel is measured as 0.45 MPa, which is also reproduced well by a numeral model, demonstrating the effectiveness of the numerical model. A modified procedure for sealing test is suggested for utility tunnel by changing the pressure increment from 0.1 MPa to 0.05 MPa; otherwise the peak internal pressure can be missed. The structural integrity of utility tunnel can be impacted by prefabrication, but leakage never occurs for the normal burial depth, unless it is beyond 13 m.